2019
DOI: 10.2147/prom.s196042
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validation study of the Parkinson&rsquo;s Fatigue Scale in advanced Parkinson&rsquo;s disease</p>

Abstract: Purpose: To validate the Parkinson’s Fatigue Scale (PFS-16) in advanced Parkinson Disease (APD) patients using the scale’s Spanish version. Patients and methods: In a clinical study for Levodopa-Carbidopa Intestinal Gel (LCIG), 59 patients were assessed over six months using the PFS-16 and other instruments. The psychometric properties of the PFS-16 were then analyzed. Results: Patients (60.7% men) were aged 68.02±7.43 years. PD duration was 12.57±5.97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…Data concerning factors associated with fatigue in PD are still scarce and contradictory. In contrast of results of the present study, some studies have found association between fatigue and education level, time from diagnosis, female gender, advanced age, severity of PD, and advanced HY disease stages 16,37,38 . Similar to the current study, low-to-high correlations were found between the fatigue (PFS-16) and depression measures 16,39,40 and anxiety assessments 16,40 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Data concerning factors associated with fatigue in PD are still scarce and contradictory. In contrast of results of the present study, some studies have found association between fatigue and education level, time from diagnosis, female gender, advanced age, severity of PD, and advanced HY disease stages 16,37,38 . Similar to the current study, low-to-high correlations were found between the fatigue (PFS-16) and depression measures 16,39,40 and anxiety assessments 16,40 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the individuals reported the dose of levodopa levels and many of them use other antiparkinsonian medicine associated. Other studies also confirmed the association of the presence or severity of fatigue (HY) and LEDD 35,36,37 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[100][101][102][103] The PFS-16 questionnaire is the only PD specific scale. 104 The PFS-16 presents self-reported data from 16 questions relating to fatigue in PD. 102 The PFS-16 is considered a reliable, responsive, and sensitive questionnaire in regards to PD-related fatigue symptoms.…”
Section: Increased Fatigue Levels In Parkinson's Diseasementioning
confidence: 99%
“…102 The PFS-16 is considered a reliable, responsive, and sensitive questionnaire in regards to PD-related fatigue symptoms. 104 One consideration to note is the diversity and specificity of fatigue rating scales utilized in PD studies. Identifying one universal fatigue scale that is used in PD trials may result in greater efficacy when comparing future studies.…”
Section: Increased Fatigue Levels In Parkinson's Diseasementioning
confidence: 99%